2017
DOI: 10.3747/co.24.3349
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab-Induced Cardiotoxicity: Testing a Clinical Risk Score in a Real-World Cardio-Oncology Population

Abstract: Background Trastuzumab has improved survival for women with her2-positive breast cancer, but its use is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 21 publications
(25 reference statements)
3
16
1
Order By: Relevance
“…In this study, the fact that repeated TZM treatment was associated with resultant marked hypertriglyceridemia without corresponding hypercholesterolemia is a strong indication that TZM could increase the risk for an adverse cardiovascular event such as angina pectoris, ischemic heart disease, cardiomyopathy, stroke, and heart failure. This assertion is in consonance with previous studies that have reported TZM to increase the risk for coronary artery disease and ischemic heart disease ( Rushton et al, 2017 ; Yuan et al, 2018 ; Montemurro et al, 2019 ; Chaturvedi et al, 2020 ). The fact that ADP, LSP, and VAL pretreatment individually attenuated TZM -associated hypertriglyceridemia is notable and indicate cardioprotective potentials of these drugs although their fixed-dose combinations worsened TZM ’s potentials for dyslipidemia and increased risk for cardiovascular events.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the fact that repeated TZM treatment was associated with resultant marked hypertriglyceridemia without corresponding hypercholesterolemia is a strong indication that TZM could increase the risk for an adverse cardiovascular event such as angina pectoris, ischemic heart disease, cardiomyopathy, stroke, and heart failure. This assertion is in consonance with previous studies that have reported TZM to increase the risk for coronary artery disease and ischemic heart disease ( Rushton et al, 2017 ; Yuan et al, 2018 ; Montemurro et al, 2019 ; Chaturvedi et al, 2020 ). The fact that ADP, LSP, and VAL pretreatment individually attenuated TZM -associated hypertriglyceridemia is notable and indicate cardioprotective potentials of these drugs although their fixed-dose combinations worsened TZM ’s potentials for dyslipidemia and increased risk for cardiovascular events.…”
Section: Discussionsupporting
confidence: 91%
“…Currently there are two CRS that have been published: the first in the seven-year follow-up of the NSABP-31 clinical trial [38] and a more recent score by Ezaz and colleagues [24]. In comparison to a study by Rushton et al who tested the use of the CRS in a Canadian patient population [25], there was a substantially smaller percentage of patients in our study who developed cardiotoxicity (43% vs 11%, respectively). This discrepancy may have been due to the differences in definition of cardiotoxicity in addition to the fact that these patients were already high risk as they were referred to a cardiooncology clinic.…”
Section: Discussioncontrasting
confidence: 51%
“…This CRS was applied to our patient population to test its value as a predictive tool for the detection of cardiotoxicity. Two sensitivity analyses as previously tested in a Canadian setting from patients referred to a cardio-oncology clinic [25] were performed in our patient dataset. The first sensitivity analysis considered a true positive (TP) as a score of ≥4 points (includes both moderate-and high-risk group) and a score of 0-3 points (low-risk group) as a true negative (TN); the second sensitivity analysis considered a TP as a score of ≥6 points (high-risk group only) and a score of 0-5 points (includes both low-and moderate risk) as a TN.…”
Section: Methodsmentioning
confidence: 99%
“…Although the score was designed and validated for the prediction of mortality in CAD patients, contingency analyses and receiver operating curves showed high sensitivity, specificity and accuracy to predict cardiotoxicity in the present study ( Table 5 ). While the advantages of the ECG score are its easy calculation and cost-effectiveness, other clinical risk scores are more complex and include parameters like age, cardiovascular risk factors and chemo-/immunotherapy doses [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%